Faktor-Faktor Pendorong Alihfungsi Lahan Sawah Menjadi Lahan Non-Pertanian (Kasus: Subak Kerdung, Kecamatan Denpasar Selatan) - Listia Dewi, Ida Ayu; Sarjana, I Made (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2015)
Land is the source of life for all creatures.  However, now the existence of the land begins shifting.  Land conversion activities are increasingly rife.  Subak, as farmer organizations for wetlands, is becoming more helpless. Economic factors that drive land use change from activities of rice farming is the low income, land owners working in other sectors, the selling price of land in Subak Kerdung, and the presence of non-agricultural business activities in this subak area.  Social factor that push for land conversion activities are adat and religious activities which require large funding sources and the desire to follow the behavior of the surrounding environment.  Institutional factors that push for land conversion activities are also concerned with institutional weaknesses of the subak itself and weak implementation of the governance of urban space.  Combating land conversion that occurs in the subak areas is not much that can be done by administrators of subak that only allow landowners to sell rice fields when destined for agricultural activities and seek smoothness for existing farming activities in the subak areas.
Keywords: lands, rice fields, switch of function, driving factors